A multi-reservoir model for projecting drought impacts on thermoelectric disruption risk across the Texas power grid. (15th September 2021) - Turner, Sean W.D.; Nelson, Kristian; Voisin, Nathalie; Tidwell, Vincent; Miara, Ariel; Dyreson, Ana; Cohen, Stuart; Mantena, Dan; Jin, Julie; Warnken, Pete; Kao, Shih-Chieh
Abstract: Thermoelectric power plants often depend on multipurpose reservoirs to supply cooling water. Although reservoirs buffer natural hydrologic variability, severe droughts can deplete storage below critical thresholds, or to levels at which the effluent water temperature exceeds the environmental compliance requirement for cooling. This study explores the effects of projected climate change and drought on water storage at 30 major reservoirs in Texas. These reservoirs collectively provide cooling water for about two thirds of thermoelectric power capacity in the Electric Reliability Council of Texas (ERCOT) power grid. Multi-ensemble runoff projections generated from eleven downscaled hydroclimate simulations are mapped to key watersheds to create spatially correlated multi-reservoir inflow sequences. These data are used to drive reservoir storage simulations, which are linked to a metric of "capacity-at-risk" using critical reservoir thresholds. We find that projected impacts of climate change are mixed, with results indicating an increase in the occurrence of thermal disruption under only half of climate models. A critical threshold of 30% storage volume—applied to all reservoirs—results in disruption to about one fifth of ERCOT thermal generation during the most severe projected droughts. The study highlights an important role for detailed reservoir behavior simulations for capturing the effects of drought and climate change on thermoelectric plant performance. Highlights: 75% of Texas thermoelectric capacity relies on reservoir water. We simulate water storage at 30 reservoirs to quantify capacity-at-risk during drought. Projected extreme droughts disrupt about one fifth of ERCOT thermal generation. Scenarios of climate change impact on thermal capacity-at-risk diverge. Known critical storage thresholds would enhance risk assessment to inform planning.